Polymeric nanoparticles containing kojic acid induce structural alterations and apoptosis-like death in Leishmania (Leishmania) amazonensis - Queiroz-Souza, Poliana; Galue-Parra, Adan; Silveira Moraes, Lienne; Macedo, Caroline Gomes; Rodrigues, Ana Paula Drummond; H. S. Marinho, Victor; H. Holanda, Fabricio; M. Ferreira, Irlon; Oliveira da Silva, Edilene (Frontiers in Pharmacology, 2024)
Leishmaniasis encompasses a cluster of neglected tropical diseases triggered by kinetoplastid phatogens nelonging to the genus Lehsmania.Leishmaniasis comprises a group of neglected tropical diseases caused by kinetoplastid pathogens of the genus Leishmania. Current therapeutic approaches are toxic, expensive, and require long-term treatment. Nanoparticles are emerginghave been suggested to represent promising potentialas a new alternative for the treatment of neglected tropical diseases treatment alternatives for reducing drug toxicity due to their controlled delivery systems. Silk Fibroin is a biocompatible and amphiphilic protein that can be used for formulating nanoemulsions, while kojic acid is a secondary metabolite with antileishmanial actions. Thus, this study evaluated the efficacy of a nanoemulsion, formulated with silk fibroin as the surfactant and containing kojic acid (NanoFKA), against promastigote and amastigote forms of Leishmania (Leishmania) amazonensis. The NanoFKA had an average particle size of 176 nm, Polydispersity Index (PDI) of 0.370, and a Zeta Potential of -32.3 mV. It presented inhibitory concentration (IC50) values of > 56 µg/mL and > 7 µg/mL for the promastigote and amastigote forms, respectively. Ultrastructural analysis, cell cycle distribution and phosphatidylserine exposure showed that NanoFKA treatment induces apoptosis-like cell death and cell cycle arrest in L. (L.) amazonensis. In addition, NanoFKA exhibited no cytotoxicity against macrophages. Given these results, NanoFKA present leishmanicidal activity against L. (L.) amazonensis.represents a promising alternative for the treatment of cutaneous leishmaniasis.